Business-education market development: main trends, barriers and prospects - Kirichok, O. V. (Journal of Economic Research & Business Administration, 2015)
Creation of effective strategy business education development in Kazakhstan is one of the key problems faced by management. Effective educational system gives opportunity to managers not only to reproduce, but also to develop the knowledge and skills, to enhance the sociocultural capital, which facilitates an innovative process. Investments into business education provides growth in social status and level of the income. The author presents her view on the trends in Business education development.